Pengaruh Motivasi Kerja Guru dan Keaktifan dalam MGMP terhadap Kreativitas Guru Ekonomi di SMA Se-Kota Malang - Rofiah, Lailatul (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
The main actor in education is a teacher. the task of the teacher is not only to enter the class, convey the subject matter, give assignments, then finish, but the teacher has the task of how the students who have diverse characteristics can be active and have creative thinking. Before transmitting their creativity to students, the teacher as an educator must know the creative potential that must be possessed. Teacher creativity can arise if the teacher is active in activities / training conducted at school or outside the school such as active activities in the MGMP, active in MGMP can arise if the teacher has high work motivation. The purpose of this study was to determine (1) the effect of teacher's work motivation on the creativity of economic teachers in high schools throughout the city of Malang, (2) the effect of MGMP activeness on the creativity of economic teachers in high schools throughout Malang, (3) the influence of teacher's work motivation and activeness in MGMP, towards the creativity of economic teachers in high schools throughout Malang. The results of this study are teacher work motivation and activeness in MGMP together have a significant effect on the creativity of economic teachers in high schools throughout Malang City. Related to this research, it is suggested that: the teacher develops his abilities and skills to prepare, implement and evaluate learning that is more creative and innovative again by following trainings carried out at school and outside the school.